Joewood (Jacquinia keyensis): Identification and Uses - Stephen Henry Brown; Marc S. Frank; Andrew K. Koeser (EDIS)
Jacquinia keyensis, known commonly as joewood, is listed as a threatened species by the state of Florida, and is most commonly found in the Florida Keys. This 8-page document discusses the identification and uses of joewood. Written by Stephen H. Brown, Marc S. Frank, and Andrew K. Koeser and published by the UF/IFAS Department of Environmental Horticulture, January 2018. http://edis.ifas.ufl.edu/ep548